Mechanism of casing failure during hydraulic fracturing: Lessons learned from a tight-oil reservoir in China. (April 2019) - Li, Yang; Liu, Wei; Yan, Wei; Deng, Jingen; Li, Haitao
Abstract: Casing failures have been systematically encountered during multi-stage hydraulic fracturing of horizontal wells in some unconventional reservoirs of China. Such failures usually manifest themselves as excessive localized radial deformation of the casing after some fracturing stages, which prevent the bridge plugs of subsequent stages from being installed to the design depths, or even result in abandonment of all remaining fracturing stages. In this paper, aiming at clarifying the casing failure mechanism during hydraulic fracturing, we performed an integrated investigation of tight-oil wells in northwest China, by analyzing the field-gained data and modeling possible mechanisms responsible for the casing failure. The investigation results show that, radial deformation of the casing due to alteration of in-situ stresses, even jointly with poor cement sheath, is far smaller than that observed in the field which could reach the order of magnitude of 1–3 cm. In contrast, we find that shear slips of pre-existing fractures/faults crossing the casing can deform the casing to the observed magnitude, justifying a conclusion that casing failure is due to the shear of pre-existing fractures/faults. This modeling-derived conclusion is supported by the records of micro-seismic events. In addition, lead impression blocks have also run for determining the deformed shape of the casing, and the results match the modeling results for the casing sheared by activated fractures/faults. Effect of fracturing pressure, in-situ stresses, length and orientation of pre-existing fractures/faults on the slippage of the fractures/faults and thus the deformation of the casing are demonstrated by a series of sensitivity studies. Additionally, some insights are derived for mitigating the casing failure in future fracturing jobs in similar unconventional reservoirs. Highlights: A statistical analysis of casing failure during multi-stage hydraulic fracturing was performed. The reduction of casing diameter was adopted as the casing-failure criterion. The reactivation of pre-existing fracture/faults may be the primary reason for casing failure during hydraulic fracturing.